The EFEK ANTI-BAKTERI EKSTRAK BIJI PEPAYA (Carica papaya L.) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS ATCC 25923 SECARA IN VITRO - Sista Satyarsa, Agung Bagus (E-Jurnal Medika Udayana; Vol 11 No 11 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i11.P04, 2022)
Staphylococcus aureus ATCC 25923 is a bacteria that has been resistant to some antibiotics and cause a serious problem in infectious disease. Therefore, an antibacterial agent is necessary to solve this problem. Papaya seeds ( Carica papaya L.) contains Flavonoid-Saponin which is very potent as an antibacterial that can be used in world health. The aim of this study is to determine the antibacterial effect of ethanol extract of papaya seed against Staphylococcus aureus ATCC 25923 . Papaya fruit is collected from one plantation in the Tabanan area, Bali. Papaya seeds were extracted by maceration method. Antibacterial test using Kirby-Bauer diffusion method. Kirby-Bauer method is created using a blank disk or disk disc. Six treatments were carried out, namely papaya seed ethanol extract with a concentration of 25%, 50%, 75% and 100%, and also with the positive control of vancomycin 30µg and the negative control of dimethyl sulfoxide (DMSO). Each treatment is repeated fourth times. Evaluation of antimicrobial activity using the agar disk diffusion method is by measuring inhibition zone diameter (mm) and this data was analyzed by SPSS. The result showed that ethanol extract of papaya seeds has an inhibition zone in agar disk. The mean score of the inhibition zone such as 25% is 6.67±0.577 mm, 50% is 9.00±1.000 mm, 75% is 10.00±1.000 mm, and 100% is 11.67±0.577 mm. Compare mean statistical test has results showed that the significant differences in all treatments (p<0.05). Based on the result, the conclusion is the extract of papaya seeds has antibacterial activity against Staphylococcus aureus ATCC 25923 bacteria.